Afrofuturism in the sequential adaptation of Kindred (2017) - Araujo Placido, Carlos Eduardo de (2024)
The sequential adaptation Kindred (2017) narrates the experiences of the protagonist, Dana, facing slavery and racism, during her various travels through time in 19th century Maryland, in the United States of America. This comic book is an adaptation of the eponymous Afrofuturistic novel by American writer Octavia E. Butler from 1979, by cartoonists Damian Duffy and John Jennings. Through intersectional representations between gender, power, and race, they more vividly illustrate the violence faced by Dana on an ancient Antebellum plantation. Therefore, the objectives of this research were to identify the main Afrofuturistic elements applied in the adaptation and verify how sequential resources were used both to intensify the reader's experience and to promote a more reliable adaptation (Cartmell, 1999). Through deconstructivist methodology (Derrida, 2010; Evans, 2020; Shaikh, 2022), we identify a profound revisionism concerning the relationships between gender, power, and race. Consequently, this revisionism has been proven in a multitude of sequential representations of historical reinterpretations, reconstructions, and reconciliations. These cartoonists do not suggest forgetting the past but understanding it as an hodiernal entity.